Blended Counselling as a Solution for the Development of Mental Health and Understanding Herd immunity for Society - Supriyanto, Agus; Mulawarman, Mulawarman; Soesanto, Soesanto; Sugiharto, Dwi Puji Yuwono; Hartini, Sri (Universitas Islam Negeri Raden Intan Lampung, 2021)
The Covid-19 (C-19) pandemic has had a significant impact on the mental health of individuals around the world. Society needs an end to the C-19 pandemic through the state of its herd immunity (HI). Significant roles counsellors in developing herd immunity and then mental health with a blended counselling strategy. This paper aims to design a counselling mix to create mental health and an understanding of herd immunity in the community. The results of the community data are fear, anxiety, anger, insomnia, and prolonged stress as a form of mental health of the community because it is socially and economically constrained. The length of time for the formation of herd immunity to prevent the C-19 pandemic is because people are worried and doubtful about vaccinations so that vaccines appear or do not trust. Significant roles counsellors in the formation of mental health through integrated counselling The implementation of face-to-face and online counselling allows the community to be more flexible and intensive according to conditions in the construction of mental health C-19 pandemic condition and post-C-19 preparations. Blended counselling as an intervention for the community in understanding herd immunity as a form supported the end of the C-19 pandemic. Integrated counselling requires the joint efforts of various relevant organizations for the science and practice of psychotherapy, psychiatry, and counsellor.